Salmonella spp. isolation from different types of egg samples and antimicrobial resistance of these strains in Argentina - Soria, Mario; Costa, Aldo Tomás; Chichi, Matías; Bruno, Susana B.; Terragno, Raquel; Tellez-Isaias, Guillermo; Bueno, Dante Javier (GMPC, 2024)
We studied the serovars present and the performance of two selective plating media, Hektoen enteric agar (HE) and Xylose-Lysine-Desoxycholate (XLD) agar, as well as the time of tetrathionate broth incubation (one and five days) used for Salmonella isolation in different samples of egg and egg packs collected from supermarkets in Argentina. We also determined the occurrence of bacterial growth inhibitors in egg content and the antibiotic resistance profile of the isolated strains. Salmonella spp. was detected in 29 samples (1.8%) from 1,643 different types of egg and egg pack samples analyzed. Eight serovars of Salmonella were isolated: S. ser. Typhimurium (ST), S. ser. Enteritidis (SE), S. ser. Agona, S. ser. Westhampton, S. ser. Brandenburg, S. ser. Gallinarum (biovar Gallinarum), S. ser. Muenchen, and S. ser. Montevideo. The most frequent were ST and SE; both were present in eggshells, yolk, and albumen. The increase in the incubation time in tetrathionate broth affected the isolation of Salmonella spp. from eggshell and pool of yolk and albumen with different values of relative sensitivity and accuracy (p<0.05). Furthermore, there was a significant difference between the two-plating media at the time of tetrathionate broth incubation in eggshell for the relative sensitivity (p<0.05). The agreement between XLD and HE agar in relation to the time of tetrathionate broth incubation depended on the type of samples studied. The occurrence of bacterial growth inhibitors in yolk and albumen depended on bacteria assayed. However, these were presented in yolk and albumen from the same pool of egg content. There were 2 and 8 different patterns of resistance among Salmonella strains isolated, and 87% of these strains were multidrug-resistant. It is necessary to understand the epidemiology of Salmonella from eggs and to alert public health to minimize the prevalence of antibiotic resistance of Salmonella spp. in Argentina.